Manage procrastination, and boss your day (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. In a survey of over 2000, 88% admitted to procrastinating for at least an hour every day, and nearly 60% admitted to doing it for more than two hours per day. If you want to make the most of your time, so that you can be more productive and more successful than your peers, take a listen to the 5 hacks in this ten-minute track. Learning Objectives Learn 5 procrastination busting hacks to supercharge your productivity Learn to take control of your time and get more from your day.